Veterinary Reproductive Ultrasonography: Advances, Applications, and Future Prospects - Laghari, Sajad Ali; Kalwar, Qudratullah; Rahimoon, Muhammad Mohsen; Hussain, Fayaz; Soomro, Fazul U Rahman; Muhammad, Taj; Saboor, Abdul; Uddin, Iqrar (BioScientific Review, 2025)
Background. Ultrasonography is a vital imaging tool in veterinary practice, particularly for reproductive assessment and pregnancy monitoring in animals. Modern ultrasound devices are compact, affordable, and efficient, facilitating their widespread clinical use. Initially applied in livestock for early pregnancy detection in the 1980s, this technique now aids in managing reproductive disorders. Despite its benefits, only a limited number of veterinarians utilize it beyond basic pregnancy diagnosis. Methods. This review examines the current literature on veterinary reproductive ultrasonography, as well as its various applications, types, modes including A-mode (1D), B-mode (2D), M-mode (motion), and Doppler (blood flow), diagnostic purposes, proper probe selection, patient preparation (hair trimming, gel application), and machine settings. Data from several studies are analyzed to summarize the uses of reproductive ultrasonography in domestic animals. Results. Ultrasonography enables early pregnancy detection (as early as Day 20-25 in small ruminants and Day 23-30 in cattle), fetal viability assessment, and sex determination (Day 55-60). It accurately monitors ovarian structures (follicles, corpus luteum) and detects reproductive disorders (endometritis, pyometra). Doppler ultrasound evaluates blood flow, while M-mode tracks fetal heart activity. This technique is safe, non-invasive, and enhances the efficiency of reproductive management. Conclusion. Ultrasonography is a safe, non-invasive, and a highly effective tool for reproductive management in veterinary medicine. It enhances early pregnancy diagnosis, fetal monitoring, and infertility management in livestock and companion animals. Despite its advantages, underutilization persists due to limited expertise among practitioners. Further research is needed to explore its long-term biological effects, though current evidence supports its diagnostic safety and reliability.